Information security awareness in university: maintaining learnability, performance and adaptability through roles of responsibility - Ahlan, Abdul Rahman; Lubis, Muharman (Research Publishing Services, 2011)
The 21st century witnesses that technology is increasingly providing availability and accessibility to information, along with this trend is the emerging problem of information security. In order to analyze how technology introduces this new risks, it is necessary to discuss the technology lifecycle. Consider for instance the technology life cycleas concerning diffusion of an innovation. Since technological innovations or IT solutions are being adopted to support business processes, the need to protect those IT solutions also arises along with its adoption. Accordingly, two important factors need much consideration in raising awareness, firstly how organization influences significantly of end user’s attitude and secondly how the organization ensure regular assessment or evaluation to measure the effectiveness of IS awareness policy within the organization.